1975
DOI: 10.1021/i360053a006
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Nitric Oxide by Monolithic-Supported Palladium-Nickel and Palladium-Ruthenium Alloys

Abstract: added to the feed stream. This experiment simulates the conditions as they would exist halfway through the reactor and bears directly on the question of ammonia intermediacy since it determines the efficiency of the catalyst to remove ammonia under reaction conditions (Bemstein, et al., 1973).The results for the ammonia addition experiments are dramatically different for the two states of the catalyst (Figure 7). Thus, most of the ammonia passes through the reactor unchanged when the catalyst is in the reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The second effect may explain the typically lower observed values of S/Ni s for single crystal Ni, which are measured at extremely low pressures (high vacuum) relative to the higher values of S/Ni s for polycrystalline and supported Ni, typically measured at orders of magnitude higher pressure; in the case of the single crystal work the surface is not in equilibrium with gas phase H 2 S/H 2 . The third effect, reconstruction of nickel surfaces by adsorbed sulfur, has been reported by a number of workers (27); for example, McCarroll and co-workers (33,34) found that sulfur adsorbed at near saturation coverage on a Ni (111) face was initially in a hexagonal pattern but upon heating above 700 K reoriented to a distorted C(2 Â 2) structure on a Ni(100) layer. In another study (32), sulfur adsorbed on a Ni(810) caused decomposition to (100) and (410) facets.…”
Section: And In Amentioning
confidence: 75%
See 2 more Smart Citations
“…The second effect may explain the typically lower observed values of S/Ni s for single crystal Ni, which are measured at extremely low pressures (high vacuum) relative to the higher values of S/Ni s for polycrystalline and supported Ni, typically measured at orders of magnitude higher pressure; in the case of the single crystal work the surface is not in equilibrium with gas phase H 2 S/H 2 . The third effect, reconstruction of nickel surfaces by adsorbed sulfur, has been reported by a number of workers (27); for example, McCarroll and co-workers (33,34) found that sulfur adsorbed at near saturation coverage on a Ni (111) face was initially in a hexagonal pattern but upon heating above 700 K reoriented to a distorted C(2 Â 2) structure on a Ni(100) layer. In another study (32), sulfur adsorbed on a Ni(810) caused decomposition to (100) and (410) facets.…”
Section: And In Amentioning
confidence: 75%
“…If so, the S/Ni s ratio at saturation would in principle be 0.5 for the reconstructed surface. In the first example above, restructuring would not affect the S/Ni s ratio at saturation, since it is 0.5 for both (100) and (111) planes; however, in the second example, the S/Ni s ratio at saturation would probably decrease, as rough planes transform to smoother ones. Nevertheless, the possibility of increases in the S/ Ni s ratio at saturation due to reconstruction cannot be ruled out.…”
Section: And In Amentioning
confidence: 93%
See 1 more Smart Citation
“…While the chemical properties of volatile metal carbonyls, oxides, and halides are well known, there is surprisingly little information available on their rates of formation during catalytic reactions. There have been no reviews on this subject and relatively few reported studies to define the effects of metal loss on catalytic activity [28,[128][129][130][131][132][133][134][135][136][137][138][139][140][141]. Most of the previous work has focused on volatilization of Ru in automotive converters [128][129][130][131]; nickel carbonyl formation in nickel catalysts during methanation of CO [133,139] or during CO chemisorption at 25 °C [28,135], and formation of Ru carbonyls during Fischer-Tropsch synthesis [136,137]; volatilization of Pt during ammonia oxidation on Pt-Rh gauze catalysts [140,141]; and volatilization of Cu from methanol synthesis and diesel soot oxidation catalysts, leading to sintering in the former and better catalyst-soot contact but also metal loss in the latter case [109].…”
Section: Reactions Of Gas/vapor With Solid To Produce Volatile Compoundsmentioning
confidence: 99%
“…Bartholomew [131] found evidence of significant (50%) Ru loss after testing of a Pd-Ru catalyst in an actual reducing automobile exhaust for 100 h, which he attributed to formation of a volatile ruthenium oxide and which was considered responsible at least in part for a significant loss (20%) of NO reduction activity. Mobile copper chloride improves catalyst-soot contact; catalyst evaporation observed [109] Shen and co-workers [133] found that Ni/Al2O3 methanation catalysts deactivate rapidly during methanation at high partial pressures of CO (>20 kPa) and temperatures below 425 °C because of Ni(CO)4 formation, diffusion, and decomposition on the support as large crystallites; under severe conditions (very high PCO and relatively low reaction temperatures) loss of nickel metal occurs.…”
Section: Reactions Of Gas/vapor With Solid To Produce Volatile Compoundsmentioning
confidence: 99%